Fabrication of Heterostructured Fe2TiO5–TiO2 Nanocages with Enhanced Photoelectrochemical Performance for Solar Energy Conversion - Zhang, Peng; Lu, Xue Feng; Luan, Deyan; Lou, Xiong Wen (David) (Angewandte Chemie International Edition, 2020)
Photocatalysts with well‐designed compositions and structures are desirable for achieving highly efficient solar‐to‐chemical energy conversion. Heterostructured semiconductor photocatalysts with advanced hollow structures possess beneficial features for promoting the activity towards photocatalytic reactions. Here we develop a facile synthetic strategy for the fabrication of Fe2TiO5–TiO2 nanocages (NCs) as anode materials in photoelectrochemical (PEC) water splitting cells. A hydrothermal reaction is performed to transform MIL‐125(Ti) nanodisks (NDs) to Ti–Fe–O NCs, which are further converted to Fe2TiO5–TiO2 NCs through a post annealing process. Owing to the compositional and structural advantages, the heterostructured Fe2TiO5–TiO2 NCs show enhanced performance for PEC water oxidation compared with TiO2 NDs, Fe2TiO5 nanoparticles (NPs) and Fe2TiO5–TiO2 NPs. Heterostructured Fe2TiO5–TiO2 nanocages are fabricated through a facile synthetic approach. With the advantages of the novel hollow heterostructure, the well‐defined FeTi2O5–TiO2 nanocages exhibit enhanced photoelectrochemical performance compared with TiO2 nanodisks, Fe2TiO5 nanoparticles, and Fe2TiO5–TiO2 nanoparticles.